Assessing plastic pollution in Brazilian aquatic ecosystems:an integrated study of pollution in organisms and environments. - Cardozo, Ana Lúcia Paz (2024)
Plastics are pervasive contaminants worldwide, accumulating from the poles to the equator, spanning pristine environments to deep ocean basins.This workexplores how seasonal variations in a floodplain influence the ingestion of plastics by freshwater fish and systematically examines trends and gaps in Brazilian research related to plastic pollution.Additionally, the potential relationship between anthropogenic activities and the amounts of plastic found in Brazilian aquatic environmentswas investigated.Among the 23 fish species analyzed in the Upper Paraná River floodplain, nine were ingested plastics, and the particles were associated with fishingactivity and domestic waste. Seasonality played a crucial role in the amounts of plastic ingested by these species, with the highest number of particles recorded during the wet season. As for trends and gaps in Brazilian research on plastic pollution, a substantial number of publications related to marine environments, microplastics, and fishwas identified. Conversely, freshwater environments and invertebrates are underexplored.Considering the distribution of studies within Brazilian biomes, the Pantanaland Cerrado had the lowest number of publications—an alarming trend considering the significant rivers and basins they house.Finally, themodels were unable to find strong and significant correlations between the number of plastics and anthropogenic activities in Brazilian municipalities.The lack of significant relationships may be attributed to the limitations of our dataset, specificallydue to the low number of studies.Nevertheless, other factors influenced the quantities of plastic detected.In biotic samples, the number of ingested plastics was influenced by the animal group, with reptiles, birds, and fish being the most affected groups. For abiotic samples, the type of environment emerged as a significant factor.In sediment samples, the quantity of plastics was higher in estuarine and freshwater environments. In water samples, the quantity of plastics was higher exclusively in freshwater environments.The finds of this workcontribute to new research on plastic pollution in Brazilian aquatic environments, expanding theunderstanding of the dynamics of plastics in freshwater environments and their interaction with various organisms.